(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents an overview of fault current limiters Fault current limiters (FCL) in electrical power systems offer the opportunity to reduce short-circuit stresses to the system in the case of faults. But as electrical power systems are normally operated without faults most of the time, FCLs must not have negative effects during these periods of normal operation. Usage of renewable energy to meet demand without proper synchronization will result in power quality problems like voltage sag, swell etc. Fault Current Limiters offers a possible solution to the electrical network